ROLE OF CO2 GAS EMISSION TAX ON FOSSIL FUEL IN REDUCING ENVIRONMENTAL IMPACT â€œA PERSPECTIVE FOR INDONESIAâ€ - Kemas Fachruddin; Akhmad Fauzi; Ahmad Bey; Surjono H Surtjahjo (Scientific Contributions Oil and Gas, 2007)
In the year 2001, Indonesia was ranked 21st in producing CO2 emissions. In 1990 thetotal emission of CO2 from the burning of fossil fuel was estimated at 83.8 million tonnesand by the end of the year 2020 the total emissions are estimated to be 368.3 milliontonnes. Currently, Indonesia has no specific regulation in place for controlling CO2 emissionseither in the form of an act or government regulation.Some approaches in controlling such emissions are through â€œcommon and controlâ€and or â€œmarket based instrumentâ€ (sometimes this term is called â€œeconomic instrumentâ€).Based on experience from developed countries, economic instrument in the form of carbontax or emission tax is preferred due to itâ€™s effectiveness compared with the commonand control instrument.This empirical study is intended to analyze the role of economic instrument in the formof a carbon or emission tax on the energy of fossil fuel through a modified DICE (DynamicIntegrated Model of Climate Change and the Economy). The DICE model is alsocalled a â€œThree â€“Box Modelâ€ or â€œTwo Folded Modelâ€By using some rate of social preference (R), the model outcome suggests that appropriateoptimal taxes for petrol and coal are if model using R value of 5%. Value of carbon taxper ton in optimal condition for period of 1990-2019 is within the range $US3.90 â€“ 40.35or $US1.06 -11.00 USD CO2 per ton. The price is equivalent to $US 0.002 â€“ 0.024 perliter petrol and $US 1.95 -20.25 per ton coal.Based on the model output it is indicated that carbon or emission tax with optimalscenario has no significant impact on income per capita relative to â€œBase Caseâ€. Shouldthe government apply tax instruments with optimal scenario, revenue of emission taxes willfall between $US 457.6 â€“ 2,362.8 million for period 1990-2019. The revenue consists of$US 376.1 â€“ 1,585.6 million generated from petrol and $US 81.4 â€“ 777.2 million fromcoal.